2003
DOI: 10.1080/00071660310001616228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the coagulation profile of Fatty Liver Haemorrhagic Syndrome-susceptible laying hens and normal laying hens

Abstract: 1. The rate of thrombin generation in plasma from Fatty Liver Haemorrhagic Syndrome-susceptible laying hens (FLHS, UCD-003) is more rapid than in plasma from age-matched normal Single Comb White Leghorn (SCWL) laying hens. 2. The rate of thrombin generation in plasma was determined by measuring the biological activity of the specific coagulation proteins, Factors V, VII, VIII, IX and X. 3. The higher activity of Factors V, VII and X in FLHS-susceptible laying hens compared with normal SCWL hens remained consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
(22 reference statements)
1
19
0
1
Order By: Relevance
“…It was previously suggested that increased BW has a great impact on hen mortality and in most of cases is associated with fatty livers and FLHS (Harms et al, 1972;Pearson and Butler, 1978c;Schumann et al, 2003;Walzem et al, 1993). Moreover, one of the most obvious clinical signs of FLHS is overweight of hens (typically 25%) and, if associated with sudden death of hens, sudden drop in egg production and pale comb and wattles (Couch, 1956;Crespo and Shivaprasad, 2003;Ivy and Nesheim, 1973;Julian, 2005;Lumeij, 1994;Thomson et al, 2003), could be warning signs of the presence of FLHS in a flock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously suggested that increased BW has a great impact on hen mortality and in most of cases is associated with fatty livers and FLHS (Harms et al, 1972;Pearson and Butler, 1978c;Schumann et al, 2003;Walzem et al, 1993). Moreover, one of the most obvious clinical signs of FLHS is overweight of hens (typically 25%) and, if associated with sudden death of hens, sudden drop in egg production and pale comb and wattles (Couch, 1956;Crespo and Shivaprasad, 2003;Ivy and Nesheim, 1973;Julian, 2005;Lumeij, 1994;Thomson et al, 2003), could be warning signs of the presence of FLHS in a flock.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that hens with normal comb colour still had liver haemorrhage, indicating that comb appearance alone is not completely indicative of FLHS. No definitive diagnostic criterion has been determined for FLHS in live birds, so the diagnosis is usually made at necropsy (Couch, 1956;Grimes et al, 1991;Meijering, 1979;Squires and Leeson, 1988;Thomson et al, 2003).…”
Section: Monitoring and Control Of Flhs In Laying Flocksmentioning
confidence: 99%
“…Furthermore, with the excessive amount of fat present in the liver of laying hens affected with FLHS, an understanding of how lipids influence avian haemostasis is important. Thomson et al (2003) were the first authors to investigate blood coagulation abnormalities as a potential cause for FLHS. They demonstrated that an inbred strain of laying hens (UCD-003) that is FLHS-susceptible have different haemostatic parameters compared to normal laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…They provided evidence that activities of FV, FVII and FX were reduced when lipids were depleted from plasma. Thomson et al (2003) also determined the phospholipid and fatty acid composition in thrombocyte-poor plasma for normal and FLHS-susceptible birds to investigate whether the plasma phospholipid composition was correlated with haemostatic activity. They found that normal laying hens contained linolenic acid (C18:3n3) in phosphatidylethanolamine (PE), while FLHS-susceptible laying hens contained eicosatrienoic acid (C20:3n3).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive hepatic lipid deposition in chicken can cause steatosis and fatty liver hemorrhagic syndrome (FLHS), which is characterized by obesity, an acute drop in egg production, and sudden death from hepatic rupture and hemorrhage (Wolford and Polin, 1972;Thomson et al, 2003;Yeh et al, 2009). Certain traits have been associated with FLHS; a greater prevalence of FLHS was observed in heavier birds, taking the age and phase of production into consideration (Meijering, 1979).…”
Section: Introductionmentioning
confidence: 99%